Integrative Mathematics: Mathematical Concepts in Hadiths with the Theme of Uqiyah - Muhammad Zia Alghar; Aam Choirotul Cholidiyah; Dwi Setiawati Radjak (West Science Islamic Studies, 2023)
The study of Islamic-integrated mathematics has goals that align with national education's goals, namely creating students who are devoted to God Almighty and have noble character. Islamic-integrated mathematics plays a role in collaborating mathematical concepts derived from the Quran and hadith. In the books of hadith, the discussion of uqiyah is always related to mathematical concepts. This study aims to explore the mathematical concepts contained in the uqiyah-themed traditions. A qualitative method with a literature review approach was used in this research. Data were obtained from analysing relevant books, books of hadith, journal articles, and proceedings. The results of this study revealed the existence of the concept of linear equation, the idea of equivalent comparison, the concept of function, and the concept of equation of a line through two points in the hadith related to uqiyah. In addition, examples of the application of mathematical integration in elementary and junior high school mathematics problems are presented